PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP MOTIVASI KERJA PEGAWAI DI KECAMATAN RASANAE TIMUR - Sapril Sapril; Jaenab Jaenab; Rahmatia Rahmatia (CV. Denasya Smart Publisher, 2026)
This study aims to examine the influence of transformational leadership on employee work motivation at Rasanae Timur District. The type of research used is associative research with a quantitative approach. The population in this study consisted of 72 employees of Rasanae Timur District, with a sample of 32 civil servants selected using purposive sampling. Data collection techniques included observation, questionnaires, and literature study, while data analysis was carried out using validity tests, reliability tests, simple linear regression, correlation analysis, coefficient of determination, and t-test. The results showed that transformational leadership had no significant effect on employee work motivation. This was indicated by a significance value of 0.401 > 0.05 and a t-value of 0.852 < t-table of 1.697. Therefore, the hypothesis stating a significant influence was rejected. The study concludes that other factors beyond transformational leadership play a more dominant role in influencing employee work motivation in Rasanae Timur District.